An economic analysis of public housing in Singapore - Chew, Christine Mei Ling (2014)
This project is to conduct a study on the public housing system in Singapore and to under its demand and supply mechanism. The study is important as a large part of the population is housed in HDB flats and the public housing program has become an integral part of the present society.